Uwagi o stanie i potrzebach badań nad uzbrojeniem na terenie Barbaricum w okresie wpływów rzymskich - Kaczanowski, Piotr (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
Cultural transformations caused by the latenization at the beginning of early pre-Roman period brought fundamental changes in the quantity and character of archaeological sources from the territories of the European Barbaricum. Consequently, our cognitive possibilities as fаг as reconstruction of history of the territories of central and northern Europe is concerned significantly increased, in comparison to former chronological period of Iron Age. The above remarks also refer to armament. Finds from the younger pre-Roman period, grave material particularly, allowed to undertake broader studies on armament of tribes inhabiting the territories of central and northern Europe. The finds of weapons are treated by archaeologists who deal with the late Laten and Roman issues mainly as sources enabling studies on chronology. Despite relatively high level of advancement of studies on typology and chronology of weapons from the younger pre-Roman period and the period of Roman influences it would be difficult to consider the state of researches as satisfactory. The problem of martial arts, in a broad sense of the word, of tribes inhabiting the European Barbaricum have not been subjected to detailed analyses so far. Few publications on this topic arc either of a very general character or just contributory and range of these studies does not reflect the importance of the issue. Most of the studies include numerous simplifications, not to say errors, mainly of methodological nature, particularly as far as chronology is concerned. Many of grave units less richly furnished and thus devoid of good date-makers are often mechanically assigned to wide chronological periods, whereas the inventories of fuller sets of weapons, richer and consequently better dated, are analysed within narrower phases or even sub-phases, which hardly corresponds to the life time of more than two generations. Despite the above described reservations we have a rich source base, allowing to make attempts to reconstruct armament and, at least partly, fighting techniques among the population inhabiting the European Barbaricum. The author of the paper describes a variety of military finds and conducts a thorough analysis of their location and origin. He deals with problems related to import of weapons from the territory of the Roman Empire in respective chronological periods and in various territories.